Development of a Web-Based Extracurricular Activity Monitoring Information System - Nada Kusumawardani; Pratomo Setiaji; Wiwit Agus Triyanto (Universitas Islam Indragiri, 2026)
Extracurricular activities play an important role in supporting students’ development, both in academic and non-academic aspects. However, the management of extracurricular activities in many schools is still conducted manually, making it difficult to monitor student participation, record attendance, and document achievements. This study aims to develop a web-based extracurricular activity monitoring information system to improve the effectiveness of activity management at SMP 2 Jati. The system development method used is the Waterfall model, which includes the stages of requirements analysis, system design, implementation, and testing. The system was developed using native PHP and MySQL and can be accessed by administrators, extracurricular supervisors, and students. The results of testing using the Black Box Testing method indicate that all system functions operate as intended. In addition, user evaluation using a Likert-scale questionnaire shows that the system has good usability, improves the efficiency of activity management, and provides a positive level of user satisfaction. The findings of this study demonstrate that the developed system can support a more effective and structured monitoring process for extracurricular activities.